Nutrition-Related considerations for health and performance in female Volleyball - Miguel-Ortega, Á.; Calleja-González, J.; Mielgo-Ayuso, J. (Journal of Human Sport & Exercise, 2023)
Although Volleyball is one of the most widely played sports in the World, there is little scientific information on how the ergo nutritional practice of female players should be designed. Therefore, the main aim of this narrative review is to resolute concise nutritional recommendations for volleyball women who players. Research databases such as PubMed, Scielo, Scopus, Medline or Academic Search Complete summarize and synthesize the recent evidence on the role of nutrition and its relationship with health and performance in this sporting discipline. Based on a literature review, we highlight that the individual adjustment of the energy value of the diet is one of the key factors for the physical performance of female volleyball players. An adequate intake of macronutrients allows for the achievement of correct energy values. To improve training adaptation, between 1.6 and 2.2 g·(kg·day)-1 of protein should be consumed. For optimal pre-competition muscle glycogen storage, 6-10 g·(kg·day)-1 of carbohydrates should be consumed, and 7- 10 g·(kg·day)-1 of carbohydrates should be consumed for adequate recovery. Micronutrients should be consumed in amounts corresponding to the recommended dietary allowances. Women volleyball players should take particular attention to the most adequate intake of these micronutrients, as well as vitamins such as iron, calcium, and vitamin D. Proper fluid intake, according to the player's needs, is crucial to maximize exercise performance. The diet of a female athlete is often characterized by low energy values, which increases the risk of various health consequences related to low energy availability. This diet of volleyball players must therefore be controlled carefully.